Parâmetros de qualidade em linguiça de frango do tipo frescal comercializada a granel - Santana, Flávio Estefferson de Oliveira (Universidade Federal Rural do Semi-Árido, 2021)
Sausages are meat products that are highly consumed by the population, mainly due to the ease and speed of preparation. The present study aimed to evaluate the qualitative parameters of fresh chicken sausage marketed in a municipality in the Semi-Arid region of the State of Rio Grande do Norte, carrying out physical-chemical, microbiological and parasitological analyzes. The moisture content, pH, titratable acidity, water retention capacity (CRA), cooking weight loss (PPC), shear strength (FC) and colorimetry were evaluated. Research on helminth eggs or larvae was carried out and microbiological evaluations of aerobic mesophilic bacteria, molds and yeasts, total and thermotolerant coliforms and Salmonella spp. The pH presented 33% (5/15) of the samples as recommended by the current legislation. The averages obtained for the parameters of titratable acidity, FC, PPC and CRA were 4.28%, 1.84%, 37.74% and 43.87%, respectively. Important determinations for the evaluation of sausage processing and conservation status. In colorimetry, the parameters b * (blue / yellow) were higher than those of a * (red content), thus indicating a yellowish color and the results of L * (luminosity) obtained a white direction. The values of aerobic mesophilic bacteria ranged from 4.44 to 7.75 log10UFC/g (Colony Forming Unit per gram), indicating that contamination of the product occurred in some stage of processing, distribution, storage or commercialization. A percentage of 93% (14/15) of the samples from the group of thermotolerant coliforms was within the recommended for consumption. For Samonella spp., There was no contamination in all samples. Thus, it was possible to perceive that the commercialized chicken sausages are mostly adequate in terms of quality, however, even more care is needed in marketing and storage to avoid the development of undesirable microorganisms
Keywords: Análises de alimento; Produto cárneo; Segurança alimentar; Food analysis; Food safety; Meat product; CIENCIAS AGRARIAS::ZOOTECNIA